Rancang Bangun Aplikasi Tes Minat dan Bakat Berbasis Web dengan Pendekatan Scrum - Jeffry, Jeffry; Marcel, Marcel (Maranatha University Press, 2024)
The selection of majors that align with students' interests and talents plays a crucial role in determining their academic success and future careers. However, the Faculty of Psychology faces significant challenges related to the efficiency of the interest-aptitude testing process and the quality of counseling services. Conventional approaches relying on manual forms and booklets have proven to be ineffective and time-consuming. Therefore, this research introduces an innovative solution in the form of a web-based interest test application designed using the agile scrum method. This application is designed to implement the RIASEC theory (Realistic, Investigative, Artistic, Social, Enterprising, and Conventional), which helps identify students' interests based on various types of interests and talents. The RIASEC theory offers a comprehensive framework for understanding students' interest tendencies, subsequently facilitating more accurate major selection. The agile scrum method was chosen to ensure the iterative development of the application and responsiveness to user feedback, thereby making it adaptable to the specific needs of the Faculty of Psychology. In initial testing, this application has shown the potential to improve the efficiency of the interest-aptitude testing process and the quality of counseling services. Features such as an intuitive user interface, automated data processing, and detailed test result reports are expected to reduce the time and resources required in the conventional process. Additionally, this application also allows easier access for students to take interest-aptitude tests anytime and anywhere, thus expanding the reach of counseling services. With this solution, it is hoped that the Faculty of Psychology can address existing constraints and provide more effective and efficient services in assisting students in selecting majors that align with their interests and talents. This application not only provides technological solutions but also contributes to improving the quality of education and career development for students in the future.